Extension of Stunting Prevention through Posyandu Program of Murukan Village Mojoagung Subdistrict - Ilmul Ma’arif; Bayu Irawan; Laili Dwi Utami; Fitri Nur Laili (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
In 2021 Murukan village is the village with the highest percentage of babies who experience stunting in Jombang regency which is 41.2% or recorded 103 stunting babies but decreased by 7.39% or recorded as much as 25.6 in 2021. Stunting is a condition of failure to grow in children under five due to chronic malnutrition so that the child becomes too short for his age. The method used in Community Service is Community Organisation Community Development (COCD) which is an approach method where it considers that community change or development can be done well through an active participation of partner communities. The results of data activities obtained from questionnaires distributed to teenagers in murukan village for understanding of the picture of stunting prevention in murukan village following the following data: previous behavior with a value of 66.23%, Benefits of Action with a value of 61.75 %, Obstacles to Action with a value of 65.09 %, Stunting prevention behavior with a value of 75. This Community Service activity benefits in terms of increasing knowledge about stunting.